Open Science Alternatives to Scopus and the Web of Science: A Case Study in Regional Resilience - Irina D. Turgel; Olga A. Chernova (Publications)
The recent years have seen increasing support for open science in academic circles. However, the large number of scientometric databases calls into question the comparability of the search and analysis tools they provide. Using the subject area of regional resilience as an example, in this study, the aim was to analyze the capabilities of widely used databases to serve as alternatives to Scopus and Web of Science in solving research problems. As alternatives, in the present article, the following open, free scientometric databases were considered: AMiner, Wizdom.ai, the Lens, Dimensions, and OpenAlex. Their capabilities were demonstrated for the subject area under study, and the obtained results were compared. The study results showed that alternative databases provide essential data on trends in scientific development. It is noteworthy that they largely replicate the provided data, supplementing and expanding them by using different types of data sources. However, open databases do not guarantee a high quality of materials and exhibit a relatively low level of metadata. Thus, it is premature to abandon the use of Scopus and Web of Science in research activities. Since scientometric databases were developed in different contexts, they are characterized by structural and functional heterogeneity, which complicates their comparison. Therefore, a selective approach should be adopted for the choice of scientometric databases, taking into account financial and other constraints, as well as the specifics of research problems.